Comparing Rotational Stability Over Time Between Four Monofocal Toric Intraocular Lenses - Hoffmann P; Potvin R; Anello RD; Hengerer F; Auffarth G; Guldenfels Y; Bertelmann E; Ruiz Mesa R; Fischinger I; Krawczyk S; Seitz B; Antolin-Garcia D; et al. (Clinical Ophthalmology)
Peter Hoffmann,1 Richard Potvin,2 Robert D Anello,3 Fritz Hengerer,4 Gerd Auffarth,5 Yves Guldenfels,6 Eckart Bertelmann,7 Ramon Ruiz Mesa,8 Isaak Fischinger,9 Sandra Krawczyk,10 Berthold Seitz,11 David Antolin-Garcia,12 Stefanie Schmickler,13 Louis Hoffart,14 Thomas Kohnen,15 Alvin S Relucio3 1Augen- und Laserklinik Castrop-Rauxel GmbH, Castrop-Rauxel, Germany; 2Science in Vision, Frisco, Texas, USA; 3HOYA Surgical Optics, Irvine, California, USA; 4Augenklinik, Bürgerhospital, Frankfurt, Germansy; 5Universitäts-Augenklinik Heidelberg, Heidelberg, Germany; 6La Clinique Rhena, Strasbourg, France; 7Charité – Universitätsmedizin Berlin, Berlin, Germany; 8Clínica OFTALVIST Ophthalmologie in Jerez de la Frontera, Jerez de la Frontera, Spain; 9Berlin Eye Research Institute, Berlin, Germany; 10Klinikum Stuttgart – Katharinenhospital, Stuttgart, Germany; 11Universitätsklinikum des Saarlandes Klinik für Augenheilkunde, Homburg/Saar, Germany; 12Hospital La Milagrosa Servicio de Ofthalmología, Madrid, Spain; 13Augen-Zentrum-Nordwest, Ahaus, Germany; 14Centre Vision Sud, Marseille, France; 15Universitätsklinikum Frankfurt, Frankfurt, GermanyCorrespondence: Robert D Anello, HOYA Surgical Optics 110 Progress, Suite 175, Irvine, CA, 92618, USA, Tel +1-909-224-6149, Email bob.anello@hoya.comPurpose: To evaluate the rotational stability of four different monofocal toric intraocular lenses (IOLs) from surgery to 4– 6 months postoperative.Methods: This was a subset of data from a prospective multi-center randomized clinical study. High resolution retro-illuminated images of eyes implanted with four different toric IOLs were obtained immediately after surgery, and at 1 day, 1 week, 1 month and 4– 6 months after surgery. Fixed scleral features were identified in the surgical image. An independent reading center evaluated the orientation of the IOL from all images, based on the angle between the toric axis marks and these fixed scleral landmarks. Rotational stability was determined by calculating differences in orientation between visits.Results: Digital images from 299 eyes implanted with one of the four IOLs were available for analysis. Orientation data were successfully determined in about 90% of images. Biometry and IOL orientation were not significantly associated with IOL rotation. The Vivinex lens showed the lowest absolute rotation, with a mean value less than 1.5 degrees at all time intervals measured, with a maximum standard deviation of 1.4 degrees. The AcrySof lens was next lowest, with an absolute rotation below two degrees for all intervals. Mean absolute rotation for the Tecnis lens was significantly higher than for the other IOLs (> 2 degrees for all intervals). For the AcrySof and Vivinex lenses, there were no reported rotations > 10 degrees for any interval; 97% or more of results were < 5 degrees, compared to 93% for the AT Torbi lens and 90% for the Tecnis lens. Only 6 lenses (4 Tecnis: 8.3%, 2 AT Torbi: 4.3%) had a rotation > 10 degrees at any time point.Conclusion: Rotational stability appeared excellent for the Vivinex and AcrySof toric IOLs, with slightly more variable performance evident with the AT Torbi and Tecnis IOLs.Keywords: toric, Vivinex™, XY1A, XY1-SP, AcrySof™ SN6ATx, Tecnis™ Toric ZCT, AT Torbi™, rotation, Astigmatism